2022
DOI: 10.1101/2022.04.28.489875
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Complete sequences of six Major Histocompatibility Complex haplotypes, including all the major MHC class II structures

Abstract: Accurate and comprehensive immunogenetic reference panels are key to the successful implementation of population-scale immunogenomics. The 5Mbp Major Histocompatibility Complex (MHC) is the most polymorphic region of the human genome and associated with multiple immune-mediated diseases, transplant matching and therapy responses. Analysis of MHC genetic variation is severely complicated by complex patterns of sequence variation, linkage disequilibrium and a lack of fully resolved MHC reference haplotypes, incr… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(31 citation statements)
references
References 70 publications
0
27
0
Order By: Relevance
“…Initially, only two haplotypes were resolved completely at the base pair level (cell-lines PGF and COX); whereas the other six haplotypes were completed only at 51% (cell-line APD) to 93% (cell-line QBL) of the MHC genomic region. Seven of the SCMHP cell-lines were resequenced again as part of 95 near-complete haplotypes, using short-range and long-range NGS 11,49 . Overall, Norman et al provided 137 genotyped loci for most of the 95 celllines that they sequenced 11 .…”
Section: Homozygous Cell-lines As Mhc Genomic Sequence Haplotype Refe...mentioning
confidence: 99%
See 1 more Smart Citation
“…Initially, only two haplotypes were resolved completely at the base pair level (cell-lines PGF and COX); whereas the other six haplotypes were completed only at 51% (cell-line APD) to 93% (cell-line QBL) of the MHC genomic region. Seven of the SCMHP cell-lines were resequenced again as part of 95 near-complete haplotypes, using short-range and long-range NGS 11,49 . Overall, Norman et al provided 137 genotyped loci for most of the 95 celllines that they sequenced 11 .…”
Section: Homozygous Cell-lines As Mhc Genomic Sequence Haplotype Refe...mentioning
confidence: 99%
“…The SNP count was <0.001 SNP/kb between the same HLA-A haplotypes in C and D. Spikes and peaks of SNPs above 100 SNP/kb were due mostly to nucleotide misalignments because of poor sequence assembly, structural variations, gaps, inversions or long runs of unspecified nucleotides. See recent SNP plots by Houwaart et al 49 for additional comparisons between MHC haplotypes. expression and disease, D'Antonio et al showed that eQTL analyses of HLA haplotypes provided substantially greater statistical power than only using single variants 59 .…”
Section: Block Length Bpmentioning
confidence: 99%
“…Genome assemblies generated by such a hybrid approach using Nanopore and Illumina sequencing, for example, resolved and phased HLA haplotypes with a 99% accuracy at a 3-field resolution. 99,107 Another hybrid approach using PacBio and Hi-C sequencing, which is a high-throughput chromosome conformation capture technique, resolved HLA and KIR haplotypes with a 98%-99% accuracy in comparison to reference sequences. 108 Combining WGS data obtained from both a PacBio and an ONT platform resolved HLA regions with 100% accuracy, whereas another research group using this hybrid sequencing approach defined HLA and KIR haplotypes that contained only minor errors in repeat-rich segments.…”
Section: Resolving Mhc and Kir Haplotypes As Bycatch Using Whole Geno...mentioning
confidence: 99%
“…Therefore, WGS on a PacBio or ONT platform is often combined with a short‐read method to ensure sufficient coverage that improves the accuracy. Genome assemblies generated by such a hybrid approach using Nanopore and Illumina sequencing, for example, resolved and phased HLA haplotypes with a 99% accuracy at a 3‐field resolution 99,107 . Another hybrid approach using PacBio and Hi‐C sequencing, which is a high‐throughput chromosome conformation capture technique, resolved HLA and KIR haplotypes with a 98%–99% accuracy in comparison to reference sequences 108 .…”
Section: Transcriptomic and Genomic Characterization Of Mhc And Kir F...mentioning
confidence: 99%
“…Fully phased MHC sequences are invaluable resources because they can serve as references for imputation using short reads. Very few of these sequences exist today, to our knowledge, and they are mostly derived from individuals of European ancestry 32 , so are blinded to the great diversity of HLA alleles and haplotypes in non-European populations 25,[34][35][36][37] .…”
Section: Introductionmentioning
confidence: 99%